Social, Psychological, Motivational, and Educational Effects of 6 February Earthquakes: A Qualitative Study on Teachers - Akilli, Ceyda (IGI Global, 2025)
As a result of two earthquakes with magnitudes of 7.7 Mw and 7.6 Mw in Kahramanmaras on 6 February 2023, 11 cities in Turkey were severely damaged, and over 50,000 citizens lost their lives. This study aims to explore the social, psychological, and motivational effects of these earthquakes on teachers and their impact on educational activities. A qualitative phenomenological design was used, with 46 teachers from Elazig, Malatya, and Diyarbakir, areas declared disaster zones, participating. Data was collected using a semi-structured interview form and analyzed through descriptive and content analysis. Results revealed that the earthquakes negatively impacted teachers socially, psychologically, and motivationally, leading to trauma-related disorders, phobias, and reduced professional motivation. Some female teachers, however, noted increased solidarity and empathy. The findings also showed disruptions in educational quality, decreased academic performance, increased absenteeism, and a negative shift in school climate. © 2026, IGI Global Scientific Publishing. All rights reserved.
Keywords: Teaching; Academic performance; Content analysis; Descriptive analysis; Disaster zones; Educational activities; Educational qualities; Female teachers; Qualitative study; Semi structured interviews; Teachers'; Earthquakes